The employment contract : from collective procedures to individual rights - Brown, William...[et al.] (2000)
Analyzes the institutional basis and form of the employment contract in Britain using the 1998 Workplace Employee Relations Survey. Assesses the extent to which collective bargaining still regulates pay and non-pay aspects of employment.